Gender differences in students' perceptions of teacher and peer feedback in mathematics: lessons from Denmark. (4th March 2022) - Sortkær, Bent; Reimer, David
ABSTRACT: Although a vast amount of literature on feedback practices and the effects of feedback on learning outcomes exists, very few studies include peer feedback in the analysis, and very few studies examine variations in students' perceptions of feedback. By exploiting a unique survey of feedback practices in mathematics lessons (Student Experiences of Feedback survey) among eighth and ninth graders in Denmark (N = 1, 098), we examine gender differences in how students experience three different varieties of feedback: feedback delivered by teachers, feedback delivered by peers, and feedback given to peers. We find that while boys experience the most teacher-student feedback, girls experience the most feedback from peers. Furthermore, results indicate that class composition (i.e. the gender ratio and the average socioeconomic background of peers) influences feedback practices. Our results have implications for understanding the gendered nature of the multidirectional and polyphonic feedback actions that occur on a daily basis within mathematical classrooms.